Prostate histological investigation in rats exposed to bisphenol a and phytochemicals during the perinatal period and subjected to hormonal stimulus in adulthood - Cavalleri Sousa, Thainá; de Oliveira, Camila Bonillo; Silva Ricardo, Maria Luiza; Musa de Aquino, Ariana [UNESP]; Scarano, Wellerson Rodrigo [UNESP]; Cruz Veras, Allice Santos [UNESP]; Almeida Tavares, Maria Eduarda [UNESP]; Teixeira, Giovana Rampazzo [UNESP]; Castillho, Anthony César deSousa; Pacagnelli, Francis Lopes; Zalotti Brandt, Joyce; de Oliveira Mendes, Leonardo (Taylor & Francis, 2022)
Bisphenol A (BPA) is an environmentally dispersed chemical associated with tumor development. Phytochemicals such as indole-3-carbinol (I3C) and genistein (GEN) have chemoprotective effects on tumor cells. Thus, this study aimed to evaluate the prostatic morphological aspects of rats exposed to BPA, GEN, and I3C during the perinatal period and submitted to hormonal stimulus in adulthood. Blood was collected to obtain hormone concentrations. Slides stained with hematoxylin & eosin, and picrosirius were subjected to fractal, stereological, morphometric, and collagen quantification analysis. I3C decreased the plasma dihydrotestosterone levels, and both phytochemicals increased the plasma estrogen levels. Unlike phytochemicals, BPA did not alter any of the parameters evaluated. GEN reduced the epithelial height, while I3C increased the fractal dimension and stromal collagen. Although BPA did not alter the prostate morphology, the phytochemicals provided beneficial effects for the prostate histological organization in adult animals subjected to hormonal stimulus.
Keywords: Endocrine disruptors; genistein; indole-3-carbinol